Kegiatan Magang Sebagai Profit and Revenue Growth Analyst pada PT Tirta Investama - Aurellio Fadel Nugroho; Muhammad Ghazi; RR Niken Purbasari (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
MBKM is a program by the government that aims to eliminate the skills gap between current manpower available to the industry needs. This report explains the writer’s experience during the internship program at PT Tirta Investama (Danone Indonesia) as Profit and Revenue Growth Analyst. In the program, the writer is assigned to do monthly finance reporting, involved in digitalization project, analyzed a certain business case, and built sales support dashboard. This internship experience helps the writer to develop the skills more, such as communication skills, ability to work in team, and another technical ability such as Microsoft Excel and Power BI. A few administrative technicalities should be improved in order to make this program better